2019
DOI: 10.1002/anie.201902751
|View full text |Cite
|
Sign up to set email alerts
|

Ni3N as an Active Hydrogen Oxidation Reaction Catalyst in Alkaline Medium

Abstract: Hydroxide‐exchange membrane fuel cells can potentially utilize platinum‐group‐metal (PGM)‐free electrocatalysts, offering cost and scalability advantages over more developed proton‐exchange membrane fuel cells. However, there is a lack of non‐precious electrocatalysts that are active and stable for the hydrogen oxidation reaction (HOR) relevant to hydroxide‐exchange membrane fuel cells. Here we report the discovery and development of Ni3N as an active and robust HOR catalyst in alkaline medium. A supported ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
200
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(226 citation statements)
references
References 54 publications
9
200
0
Order By: Relevance
“…TheX ANES spectrum of Sb K-edge for PC/Sb/SbPO 4 (red in Figure 2c)s hows am ain peak at 30 502 eV,w hich is similar to that of reported Sb 3+ species. [15] After the NRR testing,t he main peak slightly shifted to ah igher photon energy (blue in Figure 2c), indicating the appearance of Sb species with ah igher valence state on the surface of the catalyst, [16] which is consistent with the XPS analysis result. Theradial distribution function of PC/Sb/SbPO 4 in Figure 2d shows the peaks centered at 0.98 and 1.48 belonging to SbÀ Obonds,while the adjacent peak featured at 2.73 resulted from the SbÀSb interaction.…”
supporting
confidence: 82%
“…TheX ANES spectrum of Sb K-edge for PC/Sb/SbPO 4 (red in Figure 2c)s hows am ain peak at 30 502 eV,w hich is similar to that of reported Sb 3+ species. [15] After the NRR testing,t he main peak slightly shifted to ah igher photon energy (blue in Figure 2c), indicating the appearance of Sb species with ah igher valence state on the surface of the catalyst, [16] which is consistent with the XPS analysis result. Theradial distribution function of PC/Sb/SbPO 4 in Figure 2d shows the peaks centered at 0.98 and 1.48 belonging to SbÀ Obonds,while the adjacent peak featured at 2.73 resulted from the SbÀSb interaction.…”
supporting
confidence: 82%
“…TheX PS survey spectra both for Ni 3 N@C and Ni 3 Na re shown in Figure S2. Meanwhile,t he characteristic peak of N À Ni in Ni 3 N@C also have apositive shift from 398.0 eV to 398.4 eV, suggesting an interfacial charge transfer from Ni 3 Nt ot he carbon support in Ni 3 N@C. [21] TheO ER is the major competing reaction for the HMF electrocatalytic oxidation in an aqueous electrolyte.T herefore,t he HMF electrocatalytic oxidation performance of the Ni 3 N@C was tested by linear sweep voltammetry (LSV) in 1.0 m KOHwith athree-electrode system in asingle cell. TheN i2 pX PS spectrum of Ni 3 Nd emonstrated that the peak of 852.5 eV (Ni 2p 3/2 )c ould be assigned to Ni + in Ni 3 N. Meanwhile,the peak of about 855.8 eV corresponds to the Ni 2+ ,w hich is generated because of the partial oxidation surface of Ni 3 Ninair.…”
Section: Angewandte Chemiementioning
confidence: 94%
“…In contrast, when comparing the XPS spectrum of Ni 3 N@C with that of Ni 3 N, the characteristic peak of Ni + in Ni 3 N@C has ap ositive shift from 852.5 eV to 852.8 eV,i ndicating that the valence state of Ni species in Ni 3 N@C is higher. Meanwhile,t he characteristic peak of N À Ni in Ni 3 N@C also have apositive shift from 398.0 eV to 398.4 eV, suggesting an interfacial charge transfer from Ni 3 Nt ot he carbon support in Ni 3 N@C. [21] TheO ER is the major competing reaction for the HMF electrocatalytic oxidation in an aqueous electrolyte.T herefore,t he HMF electrocatalytic oxidation performance of the Ni 3 N@C was tested by linear sweep voltammetry (LSV) in 1.0 m KOHwith athree-electrode system in asingle cell. The LSV curves of the Ni 3 N@C electrode for HMF oxidation (10 mm HMF) and water oxidation (no HMF) were compared (Figure 3a).…”
Section: Angewandte Chemiementioning
confidence: 94%
“…The adsorption of H 2 O on Co sites during HER is monitored using operando method. Ni et al (2019) developed a hydrogen oxidation reaction (HOR) catalyst in alkaline medium based on Ni 3 N. It also exhibits activity similar to Pt for HER in alkaline medium. In situ XAS studies revealed that Ni 3 N/C is a stable catalyst in the applied bias of 0-0.25 V vs. RHE.…”
Section: In Situ/operando Xas Studies On Her Electrocatalystsmentioning
confidence: 99%